Reliable dissipative control for Markov jump systems using an event-triggered sampling information scheme. (August 2017) - Shen, Hao; Su, Lei; Wu, Zheng-Guang; Park, Ju H.
Abstract: This paper is concerned with the problem of the reliable dissipative control for Markov jump systems by using an event-triggered sampling information scheme. In order to reduce the utilization rate of communication bandwidth, the event-triggered mechanism is considered. Furthermore, the fault-tolerance and dissipativity are also taken into account in designing a controller which ensures that the resulting closed-loop system is stochastically stable and simultaneously satisfies a dissipative property in the presence of the actuator failures. In addition, some novel integral inequalities are utilized to dispose of reducing the conservatism of the obtained delay-dependent conditions. Two examples are given to show the effectiveness and the reduced conservatism of the proposed design method.